Intramuscular oxygen-ozone therapy in the treatment of low back pain - Biazzo, Alessio; Corriero, Andrea Saverio; Confalonieri, Norberto (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Intramuscular paravertebral injections of ozone are minimally invasive, safe and efficacy in reducing pain and disability. The aim of this paper is to present the early results of paravertebral lumbar ozone injections in the treatment of low back pain. Methods: Between February 2011 and December 2015, a total of 109 patients underwent intramuscular paravertebral lumbar injections of ozone due to low back pain. Of them, 42 interrupted the treatment at a medium of 5.4 injections and were lost to follow-up. Of the 67 remaining patients, only 24 answered to our questionnaire. Local and radiating pain was assessed using a 10-cm horizontal Visual Analogue Scale. Perceived functional status and disability were evaluated using the Oswestry Disability Index, administered before treatment and one month after the last injection. Results: Visual Analogue Scale reduction was demonstrated in 23 out of 29 cycles (79%) of ozone therapy. Regarding disability evaluation, Oswestry Disability Index score reduction was assessed in all except one. No complications were recorded. Our results are similar to the other reports: 79% of patients had VAS reduction of 2.3 points and all except one patient reported ODI reduction (average reduction of 9%). Conclusions: Lumbar paravertebral oxygen-ozone injections are minimally invasive, safe, cheaper and effective in relieving pain as well as disability. This technique is easy to perform, it doesn’t need computed-tomography or anesthesiologist support. We suggest its application in low back pain as first choice to replace intradiscal computed-tomography-guided infiltrations and to avoid or delay surgery.